Integration of Bioglass Into PHBV-Constructed Tissue-Engineered Cartilages to Improve Chondrogenic Properties of Cartilage Progenitor Cells - Xue, Ke; Zhang, Shuqi; Ge, Jin; Wang, Qiang; Qi, Lin; Liu, Kai (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The Poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) scaffold has proven to be a promising three-dimensional (3D) biodegradable and bioactive scaffold for the growth and proliferation of cartilage progenitor cells (CPCs). The addition of Bioglass into PHBV was reported to increase the bioactivity and mechanical properties of the bioactive materials. Methods: In the current study, the influence of the addition of Bioglass into PHBV 3D porous scaffolds on the characteristics of CPC-based tissue-engineered cartilages in vivo were compared. CPCs were seeded into 3D macroporous PHBV scaffolds and PHBV/10% Bioglass scaffolds. The CPC–scaffold constructs underwent 6 weeks in vitro chondrogenic induction culture and were then transplanted in vivo for another 6 weeks to evaluate the difference between the CPC–PHBV construct and CPC–PHBV/10% Bioglass construct in vivo. Results: Compared with the pure PHBV scaffold, the PHBV/10% Bioglass scaffold has better hydrophilicity and a higher percentage of adhered cells. The CPC–PHBV/10%Bioglass construct produced much more cartilage-like tissues with higher cartilage-relative gene expression and cartilage matrix protein production and better biomechanical performance than the CPC–PHBV construct. Conclusion: The addition of Bioglass into 3D PHBV macroporous scaffolds improves the characteristics of CPC-based tissue-engineered cartilages in vivo.